PASTEL Analysis of Micro, Small and Medium Enterprises After Covid-19 in India - Ajmera Tushar Rameshbhai; Ashvinkumar Solanki (Celebes Scholar pg, 2021)
Micro, Small and Medium Enterprises are major sector in Indian economy in relation with GDP (Gross Domestic Product), Export and Employment generation for the country. According to Ministry of Statistic and Programme Implementation (MOSPI), the share of MSME for Gross Value Added (GVA) in total GVA during the year 2016-17 was 31.8% which is considered as significant contribution to economy. As per Directorate General of Commercial Intelligence and Statistics (DGCIS) the portion of MSME related products in total export from India during 2018-19 was 48.10% with this it is indicated most important sector for economy but after declaration of lockdown due to Covid-19 that lead to major impact on MSME sector. In this study researcher try to identify the PESTEL Environment after Covid-19 and ATMA-NIRBHAR BHARAT Abhiyan initiated by Indian Government on 12th May 2020. The major finding of the study indicated major decision are taken by government of India and Atma-Nirbhar Bharta Abhiyan give boost to MSMEs in future and widely increases number of MSMEs . In India movement also started Vocal for Local that lead to strengthen MSMEs in future.